Parabacteroides goldsteinii mitigates the lipopolysaccharide-induced inflammatory response in IPEC-J2 cells - Zhang, Junjie; Li, Anjian; He, Yang; Guo, Taozong; Ge, Yixuan; Pan, Hongbin; Dong, Cuilian (Frontiers in Veterinary Science, 2025)
IntroductionThe misuse of antibiotics threatens animal health and food safety and limits the development of livestock and poultry farming. In animal husbandry, probiotics can be used as an alternative to antibiotics because of their environmental protection and high efficiency. Parabacteroides goldsteinii (PG) has positive anti-inflammatory effects in mice; however, its role in other animals remains unknown.MethodsThe results showed that cell viability with the PG supernatant was highest at a 20-fold dilution ratio. Exposure of IPEC-J2 cells to LPS (1 μg/mL) significantly increased IL-6 and IL-8 concentrations, which triggered an inflammatory response. PG attenuated the LPS-induced inflammatory response by inhibiting the release of pro-inflammatory cytokines (IL-6) and promoting the release of anti-inflammatory cytokines (IL-10). Transcriptome analysis showed that the average number of clean reads in the LPS and LPS-PG groups was 39,311,061 and 38,085,237, respectively. In total, 2,126 differentially expressed genes (DEGs) were identified between the LPS and LPS-PG groups, including 36 up-regulated and 2090 down-regulated genes. Some DEGs, such as IL-6R and NF-кB, are related to inflammation. GO analysis was used to annotate the functions of the DEGs, and the results showed that biological regulation, cellular anatomical entity, and binding were dominant. KEGG enrichment analysis showed that the DEGs were significantly enriched in the PI3K-AKT signaling pathway, protein export pathway, and antigen processing and presentation pathway.DiscussionThese results indicate that P. goldsteinii is a promising probiotic for maintaining and improving intestinal health in piglets.